2015
DOI: 10.1128/jvi.00124-15
|View full text |Cite
|
Sign up to set email alerts
|

A Mutant H3N2 Influenza Virus Uses an Alternative Activation Mechanism in TMPRSS2 Knockout Mice by Loss of an Oligosaccharide in the Hemagglutinin Stalk Region

Abstract: e The host protease TMPRSS2 plays an essential role in proteolytic activation of the influenza A virus (IAV) hemagglutinin (HA) protein possessing a monobasic cleavage site. However, after passages in TMPRSS2 knockout mice, an H3N2 subtype IAV began to undergo cleavage activation of HA, showing high virulence in the mice due to the loss of an oligosaccharide at position 8 in the HA stalk region. Thus, the H3N2 IAV acquired cleavability by an alternative HA activation mechanism/protease(s). Influenza A virus (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…A third study described an H3N2 variant that was not able to replicate in Tmprss2 À/À mice [11]. However, after serial passages in Tmprss2 À/À mice, this virus acquired a mutation in the HA stalk which led to replication and pathology in Tmprss2 À/À mice [13]. Moreover, we recently demonstrated that in Tmprss2 À/À Tmprss4 À/À double knock-out mice, replication and pathology after infection with our H3N2 isolate was strongly diminished and infected mice survived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A third study described an H3N2 variant that was not able to replicate in Tmprss2 À/À mice [11]. However, after serial passages in Tmprss2 À/À mice, this virus acquired a mutation in the HA stalk which led to replication and pathology in Tmprss2 À/À mice [13]. Moreover, we recently demonstrated that in Tmprss2 À/À Tmprss4 À/À double knock-out mice, replication and pathology after infection with our H3N2 isolate was strongly diminished and infected mice survived.…”
Section: Discussionmentioning
confidence: 99%
“…In resistant Tmprss2 À/À mice, H1-and H7-HA are not efficiently cleaved and subsequently the virus fails to spread in infected lungs and therefore does not cause pathology [10][11][12]. On the other hand, H3N2 is able to replicate in Tmprss2 À/À mice and cause mortality [10,13]. In Tmprss2 À/À Tmprss4 À/À double KO mice, replication of H3N2 is still occurring although at a strongly reduced level resulting in low mortality [14].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to WT, TMPRSS2-KO mice proved equally [15] or slightly less vulnerable [14 ] to lethal H3N2 infection. A third H3N2 strain was avirulent in TMPRSS2-KO mice but became lethal after ten passages in mice [16,18]. Since the passaged virus carried an N-glycosylation mutation at the bottom of the HA stalk region, the loss of this glycan may alter the accessibility of the cleavage loop and provide access to an alternative host protease [18].…”
Section: Host Proteases Involved In Ha0 Cleavage Activationmentioning
confidence: 99%
“…Moreover, polymorphisms in the TMPRSS2 promoter were found to be associated with the severity of influenza in humans (14). Finally, analysis of Tmprss2 knockout mice revealed that Tmprss2 is essential for spread and pathogenesis of several influenza A virus (FLUAV) subtypes (15)(16)(17), although certain H3N2 viruses seem to be able to use proteases other than TMPRSS2 for HA activation (18,19). HAT, DESC1, TMPRSS4, and other TTSP members can activate HA upon directed expression in cell culture (9, 10, 20 -23), and Tmprss4 was shown to contribute to H3N2 FLUAV spread in mice (18).…”
mentioning
confidence: 99%